A New Chaotic Map for Secure Transmission - Hamsa A. Abdullah; Hikmat N. Abdullah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The secure communication through synchronization between two identic chaotic systems have recently gained a lot of interest. To implement a robust secure system based on synchronization, there is always a need to generate new discrete dynamical systems and investigate their performances in terms of amount of randomness they have and the ability to achieve synchronization smoothly. In this work, a new chaotic system, named Nahrain, is proposed and tested for the possible use in secure transmission via chaos synchronization as well as in cryptography applications. The performance of the proposed chaotic system is tested using 0-1 test, while NIST suite tests are used to check the randomness statistical properties. The nonlinear control laws are used to verify the synchronization of master-slave parts of the proposed system. The simulation results show that Nahrain system has chaotic behavior and synchronizable, while the equivalent binary sequence of the system has excellent randomness statistical properties. The numerical results obtained using MATLAB for 0-1 test was 0.9864, and for frequency test was 0.4202, while for frequency test within a block was 0.4311. As a result, the new proposed system can be used to develop efficient encryption and synchronization algorithms for multimedia secure transmission applications.